Ecology Letters - Ecology Letters (Wiley, 2026)
Ecology Letters is a forum for the very rapid publication of the most novel research in ecology. Manuscripts relating to the ecology of all taxa, in any biome and geographic area will be considered, and priority will be given to those papers exploring or testing clearly stated hypotheses. The journal publishes concise papers that merit urgent publication by virtue of their originality, general interest and their contribution to new developments in ecology. We discourage purely descriptive papers and those merely confirming or extending results of previous work.
FI 2.12
Q1
Keywords: Life Sciences; Ecology & Organismal Biology; Acuerdos transformativos; Transformative agreements; Ecología; Ecología de comunidades; Ecología evolutiva; Biodiversidad; Interacciones ecológicas